AUTOMEDICAÇÃO ENTRE ACADÊMICOS DE ENFERMAGEM EM UMA INSTITUIÇÃO PARTICULAR DE ENSINO - Santiago Muri Gama, Alan; Ribeiro Oliveira, Márcio; Muller Beazussi, Kamila; Santiago Muri Gama, Abel (LINKSCIENCEPLACE, 2026)
Self-medication has been an important health problem. This practice can lead to poisoning, drug interactions, addiction to drugs and antimicrobial resistance. This study aimed to determine the prevalence of the practice of self-medication among nursing students. The cross-sectional study was conducted with 50 nursing students of the School San Carlos, Bom Jesus do Itabapoana, Rio de Janeiro, with the instrument application with closed questions. The prevalence of self-medication was 82.0%, and the problem more reported health was pain (85.5%). The commonly reported reason as a practical generator of self-medication was the perception that it would not need to go to the doctor (61.0%). Among the major therapeutic groups, stood out analgesics and antipyretics 43.1%. The current period graduation was associated with self-medication (p = 0.050). Conclusion: Our study showed high prevalence of self-medication compared with other research on the subject. We consider it necessary, from these findings, content insertion about the rational use of drugs, especially the risks of self in the different disciplines that make up the curriculum of the nursing course.